PENGUJIAN PERATURAN KEBIJAKAN DI INDONESIA (OBJEK KAJIAN SURAT EDARAN PEMERINTAH) - Rasji . (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
In Indonesia there are legislation and regulatory policy. Legislation has regulated positive law, while the policy regulations unregulated positively. In fact, there are regulatory policies that are contrary to the legislation or the regulatory policy on it. The problem is what can be a testing ground of regulatory policy? Who or which agency of the authority that has an ability to conduct the regulatory policy? Based on the doctrine and positive law, which became the basis of the testing of regulatory policy is legislation, regulatory policy on it, or the general principles of good governance. The competent institutions to test the regulatory policy of Supreme Court, regulatory policy, or supervisor of officials of regulatory policy. To support that is necessary to amend the Act of 1945, Law on Judicial Power, and the Law on the Supreme Court by adding authority to the Supreme Court to test the policy regulations. Keywords: policy regulation, judicial review